Stingray Habitat Use Is Dynamically Influenced by Temperature and Tides - Elston, Chantel; Cowley, Paul D.; von Brandis, Rainer G.; Lea, James (Frontiers in Marine Science, 2022)
Abiotic factors often have a large influence on the habitat use of animals in shallow marine environments. Specifically, tides may alter the physical and biological characteristics of an ecosystem while changes in temperature can cause ectothermic species to behaviorally thermoregulate. Understanding the contextual and relative influences of these abiotic factors is important in prioritizing management plans, particularly for vulnerable faunal groups like stingrays. Passive acoustic telemetry was used to track the movements of 60 stingrays at a remote and environmentally heterogeneous atoll in Seychelles. This was to determine if habitat use varied over daily, diel and tidal cycles and to investigate the environmental drivers behind these potential temporal patterns. Individuals were detected in the atoll year-round, but the extent of their movement and use of multiple habitats increased in the warmer NW-monsoon season. Habitat use varied over the diel cycle, but was inconsistent between individuals. Temperature was also found to influence stingray movements, with individuals preferring the deeper and more thermally stable lagoon habitat when extreme (hot or cold) temperature events were observed on the flats. Habitat use also varied over the tidal cycle with stingrays spending a higher proportion of time in the lagoon during the lowest tides, when movement on the flats were constrained due to shallow waters. The interplay of tides and temperature, and how these varied across diel and daily scales, dynamically influenced stingray habitat use consistently between three species in an offshore atoll.